2022
DOI: 10.3390/toxics10060311
|View full text |Cite
|
Sign up to set email alerts
|

The Bisphenols Found in the Ejaculate of Men Does Not Pass through the Testes

Abstract: Exposure to bisphenols is related to negative effects on male reproduction. The bisphenols exposure is associated with several modes of action including negative impact on the blood–testis barrier (BTB) in testes or direct effect on spermatozoa. Bisphenols have been detected in human seminal plasma, but the possible mechanism of seminal transfer of bisphenols is not clear. Some authors consider the transfer through the blood–testis barrier to be crucial. Therefore, in this work, we compared normozoospermic men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It was concluded that BPs are predominantly transported into seminal plasma not through testicular tissue, but through comparable ejaculate volume ratios that are applied similarly to other routes of transmission. Toxic bisphenols mostly reach the seminal plasma through the secretions of accessory glands and do so to a far greater extent than through testicular tissue [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that BPs are predominantly transported into seminal plasma not through testicular tissue, but through comparable ejaculate volume ratios that are applied similarly to other routes of transmission. Toxic bisphenols mostly reach the seminal plasma through the secretions of accessory glands and do so to a far greater extent than through testicular tissue [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, mutations (clastogenesis and aneugenesis being included) in germ cells are a major cause of human reproductive failure . BPs have been reported to disrupt the blood–testis barrier, which normally functions to protect the spermatogenesis from chemical interference, , and BPs have been detected in the seminal plasma. , Meanwhile, as a major component of the blood–testis barrier Sertoli cells express CYP1A1, which makes it possible for BPs to experience metabolic activation in the place of spermatogenesis and exert clastogenicity in sperm cells.…”
Section: Resultsmentioning
confidence: 99%
“…The small number of existing studies related to BPS effects in very low doses was based on BPS concentrations measured mostly in human urine (up to 6.7 ng/mL), serum (0.15 ng/mL), or seminal plasma (up to 0.85 ng/mL) ( Thayer et al, 2016 ; Jin et al, 2018 ; Smarr et al, 2018 ; Ješeta et al, 2022 ). The only study that confirmed the presence of BPS in follicular fluid (FF) was aimed at investigating its effect on somatic cells ( Amar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%